Enhancement of absorption and bioavailability of echinacoside by verapamil or clove oil - Shen JY; Yang XL; Yang ZL; Kou JP; Li F (Dove Medical Press, 2015)
Jin-Yang Shen,1,* Xiao-Lin Yang,2,* Zhong-Lin Yang,1 Jun-Ping Kou,1 Fei Li11State Key Laboratory of Natural Medicines, China Pharmaceutical University, 2Key Laboratory of Pharmaceutical and Biological Marine Resources Research and Development of Jiangsu Province, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China*These authors contributed equally to this workPurpose: This present study investigated the absorption kinetics of echinacoside (ECH) in situ and in vitro and its oral bioavailability in rats. Additional aim was to find an agent(s) to promote ECH absorption and oral bioavailability among two efflux proteins and three absorption promoters.Methods: ECH absorption behaviors were investigated by everted gut sac model in vitro and single-pass intestinal perfusion model in situ. Pharmacokinetics study was performed to investigate the influences of verapamil and clove oil on ECH bioavailability in vivo. All samples were measured at different time intervals by high performance liquid chromatography.Results: The results showed that the effective permeability coefficient (Peff) and apparent permeability coefficient of ECH were 0.83×10-6–3.23×10-6 cm/s and 2.99×10-6–9.86×10-6 cm/s, respectively. The Peff among duodenum, jejunum, and ileum were not statistically different, but they were higher than colon (P<0.01), which demonstrated that intestinal ECH absorption was poor and site dependent. Additionally, verapamil and clove oil significantly increased the jejunal Peff of ECH both in situ and in vitro. Moreover, the bioavailability of ECH in combination with verapamil and clove oil were increased by 1.37-fold (P<0.05) and 2.36-fold (P<0.001), respectively, when compared to ECH group. Overall, verapamil and clove oil facilitated ECH absorption and oral bioavailability.Conclusion: The absorption and bioavailability of ECH were enhanced by verapamil and clove oil, respectively, both in vitro and in vivo. Consequently, the combination of verapamil and clove oil with ECH will be a promising and effective approach to promote intestinal absorption and oral bioavailability of ECH.Keywords: intestinal absorption, efflux protein inhibitor, absorption promoter